The Contradictions of Conservation: Fighting Erosion in Mao-Era China, 1953–66. Issue 2 (27th February 2020) - Muscolino, Micah S
Abstract: Based on local archival documents and fieldwork conducted in Shaanxi Province's Baishui County, this article examines how large-scale water and soil conservation campaigns launched in Northwest China's Loess Plateau region during the Mao era (1949–76) affected agrarian environments and how rural communities experienced and responded to these transformations. By mobilizing rural communities to combat water and soil loss, China's leaders expected conservation to limit sedimentation along the Yellow River's lower reaches and increase agricultural yields to support their vigorous program of industrialization. Throughout the 1950s and 1960s, local opposition to these efforts to alter human interactions with the land centered on contradictions between the long-term objectives of conservation campaigns and the priority that the rural populace placed on ensuring subsistence. With residents called on to attend to conservation work instead of other production activities, divergent imperatives translated into intense competition over how to use the land and allocate labor power. Even if conservation programs in Baishui, as in other parts of China, drew on lay knowledge and practice, these environmental management policies consistently privileged the state's developmentalist agenda over the welfare of rural communities. In this manner, Mao-era water and soil conservation supported, and was inseparable from, an extractive political economy that intensified contradictions between the rural and urban, agriculture and industry. Rather than giving voice to vulnerable populations and equitably distributing costs and benefits, Mao-era water and soil conservation exacerbated the burdens placed on marginalized rural communities.